Alcoholic/Narcotic Anonymous Program Outcome: A Systematic Review - Nadya Puspita Adriana; Dipo Wicaksono (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: Recovery and long-term remission are the goals of treatment for substance use disorders. Though there are many pathways to recovery, the alcoholic/narcotic anonymous program is widely recommended for people with addiction as an adjunct to professional treatment services. However, not many studies reviewed the outcome resulting from alcoholic/ narcotic anonymous programs. This study aimed to systematically review the outcome of alcoholic/ narcotic anonymous programs. Subjects and Method: This article was a systematic review study conducted by searching for articles from online databases such as EBSCO, Google Scholar, PubMed, and Science Direct. PICO: 1) Populations: alcohol addict or illegal drug abuser who is a member or ever joined the alcohol or narcotic anonymous program; 2) Intervention: alcohol or narcotic anonymous program; 3) Comparison: alcohol or narcotic addict or illegal drug abuser who is not the member or never join the alcohol or narcotic anonymous program or etc; 4) Outcome: a variety of outcomes such as reduce of drinking. The dependent variable is the outcome of AA programs. The inclusion criteria for this study were full articles using an observational or experimental study, with the publication year from 2000 until 31st May 2023. The data extraction was focused on the relationship between AA/NA program with the outcome resulting and reported following the Preferred Reporting Items for Systematic Reviews. Results: A total of 9 articles reviewed in this study were from USA and UK. Six studies reported there is a significant relationship between attendance at the AA/ NA program with the increase in days of abstinence. Two studies explained that attending the AA/ NA program could lower the amount and frequency of illegal drug use. Only one study discussed that the AA/NA program could also lessen the depression that addiction causes. Conclusion: Our review suggested that attending the AA/ NA program has benefits such as abstinence, reduced frequency or amount of substance intake, and a reduction in depression or problems brought on by using illegal substances. Keywords: abstinence, alcoholic anonymous, alcoholism, narcotic anonymous, outcome. Correspondence: Nadya Puspita Adriana. Universitas Kusuma Husada. Jaya Wijaya No.11, Banjarsari, Central Java, Surakarta, Indonesia. Email: nadyadriana91@gmail.com. Mobile: 0821-3800-7567